Zanesljivost meritev višin smreke z višinomerom Vertex III - Kušar, Gal (Gozdarski vestnik, 2014)
In this article we analyzed usefulness of Vertex III hypsometer for measuring tree heights on the sample of 88 spruce trees on Pokljuka plateau. The optimal method for tree height measurements with Vertex III hypsometer proved to be measuring six height readings, eliminating the highest and the lowest value and calculating arithmetic mean from the remaining four. This is a good estimation of the real tree height and doesn%t differ statistically from the reference tree height, measured on a felled tree. We found out that Vertex III hypsometer, used correctly, provides reliable (%0.25 m) measurements of tree heights.
Keywords: meritve drevesne višine; ultrazvočni višinomer Vertex III; Picea abies; Pokljuka